Coopetition : how interorganizational collaboration shapes hospital innovation in competitive environments - Zhu, Ling (Cambridge : Cambridge University Press, 2021)
Public service innovation, defined as the adoption of new technology and methods of service delivery, is at the heart of public management research. Scholars have long studied public and private sector innovation as distinctive phenomena, arguing that private sector innovation aims to increase firms' competitive advantage, while public sector innovation purports to improve governance and performance. The public-private dichotomy overlooks the complex way how organizations interact with each other for service delivery. Public services are increasingly delivered through the web of collaborative networks, in which organizations compete and cooperate simultaneously. This Element explores how coopetition, namely the simultaneous presence of competition and collaboration, shapes innovation in the health care sector. Analyzing panel data of 4,000+ American hospitals from 2008 to 2017, this Element finds evidence that coopetition catalyzes the technology and service process innovation and offers practical implications on managing innovation in competitive environments.
Title from publisher's bibliographic system (viewed on 31 May 2021).
Keywords: Health services administration